Reproductive Organ of Blow Fly, Chrysomya megacephala (Diptera: Calliphoridae): Ultrastructural of Testis - Kabkaew L. Sukontason; Tarinee Chaiwong; Urai Chaisri; Hiromu Kurahashi; Michelle Sanford; Kom Sukontason (Journal of Parasitology Research)
This work presents the ultrastructure of testis of the medically important blow fly, Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) using light microscopy and electron microscopy. Reproductive organ of males was dissected to determine the testis in the pupal stage, 3-day-old flies and 7-day-old flies and observed under scanning electron microscopy (SEM) and transmission electron microscopy (TEM). SEM displayed a smooth surface which is occasionally penetrated by tracheoles. TEM of the testis in the pupal stage presents the thick testis wall covering underdeveloped cells containing a variable size of an electron-dense globule. For the 3-day-old males, the testicular wall is formed by an external layer, a peritoneal sheath, a muscular layer, a basement membrane, and a follicular epithelium. Follicular epithelium presented developing spermatozoa. Regarding the 7-day-old males, development of spermatozoa is apparent, displaying nucleus, centriolar adjunct, axoneme, and mitochondrial derivatives, with the 9 + 9 + 2 microtubule pattern of axoneme.